Effects on organ donation of transition from apnoeic-oxygenation to radioisotope brain scanning to diagnose brain death in children - James Tibballs; Sainath Raman; Peter Francis (Archives of Organ Transplantation - Peertechz Publications, 2021)
We studied rates of cadaveric organ donation on transition from apnoeic-oxygenation to radioisotope brain perfusion scanning to diagnose brain death. We studied records of children who were organ donors and/or had Technetium Tc99m Exametazine brain scans over 1989-2018. Donation after Brain Death (DBD) commenced in 1989, Donation after Circulatory Death (DCD) in 2011. Brain scanning was adopted in 2002 and apnoeic-oxygenation abandoned in 2007. In total, 95 of 1930 children (4.9%) donated organs (81 DBD, 14 DCD). During 1989-2001, with brain death diagnosed by clinical tests including apnoeic-oxygenation, 40 of 1059 children (3.8%) donated organs at average 3.1/annum. During 2002-2007 when either apnoeic-oxygenation or scanning was used, 18 of 351 children (5.1%) donated organs at average 3.0/year. During 2008-2018 with scanning in lieu of apnoeic-oxygenation, 23 of 520 children (4.4%) donated organs at average 2.1/annum. The difference in DBD rate between eras was not significant (P=0.52). Of 77 children scanned, 65(84%) were diagnosed brain dead after 1 or 2 scans, and 29 (45%) of these donated organs. Of 12 children with limited brain perfusion (not brain dead), DCD proceeded in 8 (67%). DCD or DBD (death diagnosed by scanning) was performed during 2011-2018 in 35 of 370 children (9.5%) which is significantly more (P<0.0001) than DBD (death diagnosed by apnoeic-oxygenation) in 1989-2001. Transition from apnoeic-oxygenation to scanning to diagnose brain death did not change DBD and may facilitate DCD. Brain death can be diagnosed by radionuclide scanning in lieu of apnoeic-oxygenation.